IDENTIFIKASI KENDALA DALAM PENGUASAAN BAHASA INGGRIS (Analisa Perbedaan Individu Dalam Belajar Bahasa Inggris Mahasiswa Administrasi Perkantoran 258 Politeknik LP3I Jakarta) - Retno Budiasningrum (POLITEKNIK LP3I JAKARTA, 2015)
The purpose of this study is to determine the causes of the incompetency in English speaking of AP-258 students of LP3I Bekasi. It is focused on the typical of each individual in learning English, as gender, perception, motivation, interest, attitude, and learning strategy. Based of the result, gained the percentage of motivation and interest of the respondents in learning English as: 33% respondents with high level of motivation and interest, 11 % respondents with average level of motivation and interest, 28 % respondents with less level of motivation and interest, and 28 % respondents with no motivation and interest at all. Having positive motivation and interest through English, it will be very affecting on the attitude , perception, even the learning strategy of each person in the process of learning English. On the contrary, it will be the obstacle in the learning English process. As the most respondents have negative attitude in learning English, therefore they don’t get a good result. Keywords : Motivation, Interest Of The Respondents